The Strategies of United Nations Development Programme (UNDP) With Global Environmental Facility (GEF) To Promote Sustainable Land Management - Recindy Gilang Melati (Syntax Literate, 2022)
International organizations playing a important role in overcoming various issues in the World. Based on this case UNDP is determined to assist every country in carrying out sustainable development, in this case Environmental Issues have a greater impact on the continuity of human security. This happens based on the basis of 2 things, which are the act of human activity itself or from natural changes. One of the environmental issues that are often faced in every countries is land degradation, this environmental issue is also experienced by Kenya as a country from the East African continent where many of the people depend on livelihoods from the agricultural sector especially Argo-Pastoral. The cases of land degradation with the variations state of the land type give socio-economic impacts for the people and communities whose livelihoods depend on the land. The existence of an international organization which is UNDP as a means to help environmental issue in Kenya land degradation by applying a sustainable land management system. In this study the author will conduct a study with the aim of analyzing the strategy of the International Organization, which UNDP in applying a sustainable land management system in cases of land degradation so that it can provide results for the production system of the Argo-Pastoral. This research is taken from the UNDP and GEF projects that have been ongoing from 2011-2016 with the name Mainstreaming Sustainable Land Management in Argo-Pastoral Production System of Kenya